Comparative Analysis of the Practice of Internet Use in the Marketing Activities of Higher Education Institutions in Poland and Ukraine - Artur Kisiołek; Oleh Karyy; Liubov Halkiv (Comparative Economic Research. Central and Eastern Europe, 2020)
In the information age, the role of higher education as a factor of social progress is increasing. The competition among higher education institutions is also growing. This requires higher education institutions' (HEIs) marketing policies to be diversified, digitalized, and integrated into the virtual space. In order to find out the role and importance of Internet tools and in marketing activities, a questionnaire survey was conducted among managers and specialists of HEIs in Ukraine and Poland. The data served as the basis to study the level of variation, structure similarity, and consistency of the generalized responses of the respondents of the two countries. We verified hypotheses about (1) the absence of significant differences between the estimates of the role of the Internet in the marketing activities of HEIs in Poland and Ukraine; (2) the consistency of answers of the respondents of the two countries regarding the use of the Internet in market activites of HEIs; (3) HEIs' use mostly geo-targeting potential consumers of higher education online. The dominant feature of the Internet - quick access to information - enables effective marketing activities. The management of HEIs should increase the awareness of their marketing staff in using the Internet to expand the delivery of educational services, intensify interviewing practices for obtaining feedback from customers, attract sponsors, promote their own brands, do market research, and so on.
Keywords: I23; M3; P52; 330; higher education institution; marketing activity; Internet-marketing; marketing communications; structure similarities; variations; rank correlation